Criminal Liability for PT (Corporation) Causeing the Exceeding of Environmental Standard According Law No 32/2009 on Environmental Protection and Management - Aulia Pratiwi, Syahfitri; Syahrin, Alvi; Rizky, Fajar Khaify (Universitas Medan Area, 2025)
This study aims to analyze legal regulations, forms of criminal liability, and legal considerations of judges regarding business entities that commit environmental pollution exceeding the established quality standards. A good and healthy environment is a fundamental right of every citizen as guaranteed in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia and further regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. However, in practice, environmental pollution by business entities still frequently occurs, thus giving rise to legal issues related to the effectiveness of enforcing corporate criminal liability. This study uses a normative juridical research method with a descriptive analytical nature, a statutory regulatory approach, and case studies. Research data were obtained through literature studies covering relevant laws and regulations, legal documents, books, dictionaries, mass media, and internet sources, then analyzed qualitatively. The results of the study indicate that: (1) legal regulations related to violations of environmental quality standards normatively reflect the values ​​of justice, legal certainty, and legal benefits, but the effectiveness of their implementation still depends on coordination between law enforcement agencies; (2) the criminal liability of business entities is based on the provisions of Article 116 of Law Number 32 of 2009 which allows for the prosecution of legal entities and/or their managers; and (3) the legal considerations of judges in decisions regarding the criminal liability of business entities are based on the application of positive law while still paying attention to the values ​​of justice, benefit and legal certainty.